Field notes contributed by Stephen J. Dinsmore, summer 1984 - Dinsmore, James J.et al (1984)
Field notes were contributed by Stephen J. Dinsmore, summer 1984. Other observers were James J. Dinsmore and Erik Munson. Among the 24 species sighted were a Double-crested Cormorant in Fremont County, a Red-necked Phalarope in Story County, and Louisiana Waterthrushes at Ledges State Park. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1984. Epson - sheet feed/flatbed